The Amsterdam Modeling Suite - Baerends, Evert Jan; Aguirre, Nestor F; Austin, Nick D; Autschbach, Jochen; Bickelhaupt, F Matthias; Bulo, Rosa; Cappelli, Chiara; van Duin, Adri C T; Egidi, Franco; Fonseca Guerra, Célia; Förster, Arno; Franchini, Mirko; et al. (The Journal of chemical physics, 2025)
In this paper, we present the Amsterdam Modeling Suite (AMS), a comprehensive software platform designed to support advanced molecular and materials simulations across a wide range of chemical and physical systems. AMS integrates cutting-edge quantum chemical methods, including Density Functional Theory (DFT) and time-dependent DFT, with molecular mechanics, fluid thermodynamics, machine learning techniques, and more, to enable multi-scale modeling of complex chemical systems. Its design philosophy allows for seamless coupling between components, facilitating simulations that range from small molecules to complex biomolecular and solid-state systems, making it a versatile tool for tackling interdisciplinary challenges, both in industry and in academia. The suite also emphasizes user accessibility, with an intuitive graphical interface, extensive scripting capabilities, and compatibility with high-performance computing environments.